The Effort Factor: An Adjustment to our Understanding of Social-Ecological Metabolism in the Era of Peak Oil. (7th October 2017) - Davidson, Debra J
Abstract: The size of our ecological footprint is often attributed to those social processes governing the consumption of material resources, reflecting the tendency within sociology to pay far more attention to our social constructions of nature, and our effects on nature, but far less attention to natural processes themselves. However, our level of ecological disruption is, more precisely, a function of the effort required to exploit natural resources and convert them into the things we value for use and exchange. As the quality of those resources declines in response to historic exploitation, effort increases, and hence so does our ecological impact, a tendency that interacts with social processes to produce emergent outcomes. This effort factor constitutes an important but largely overlooked feature of social-ecological metabolic relations, one that can offer fruitful opportunities for advances in scholarship in environmental sociology, and for environmental monitoring and mediation efforts by states and civil societies. The effort factor constitutes an important causal mechanism in our socioecological relations, the effects of which are best conceived through the lens of critical realism. This article offers a conceptual elaboration of the effort factor, and a case study analysis with reference to the historical development of oil, with particular emphasis on Alberta, Canada, which highlights the disruptive tendencies embodied in our current fossil fuel-dependent socioeconomic systems.